Validity of Arbitrage Pricing Theory (APT) and its Comparison with CAPM - Satapathy, Amitabh (Indian Journal of Finance, 2026)
Purpose : This study investigated the validity of the Arbitrage Pricing Theory (APT) in the Indian capital market and compared its explanatory power with the capital asset pricing model (CAPM). Methodology : Using monthly data spanning seven years (2017–2023), the study analyzed excess returns of 15 large-cap stocks and the NIFTY index. Five macroeconomic factors: GDP growth rate, Index of Industrial Production (IIP), inflation, interest rate, and exchange rate, were selected from the literature and validated using the principal component analysis (PCA). A multivariate regression framework was employed to assess the explanatory power of APT, while CAPM was tested using market returns as the sole factor. The analysis focused on three key statistical indicators: the R2 value to assess the model’s explanatory strength, the F-test for overall model significance, and p-values for the statistical significance of each independent variable. Findings : The findings indicated that APT demonstrated weak explanatory power, with consistently low R2 values and statistically insignificant coefficients for most macroeconomic variables. In contrast, CAPM exhibited relatively higher explanatory strength across all securities. Practical Implications : The study contributed to the limited and inconclusive evidence on APT in the Indian context by providing a direct empirical comparison with CAPM. The results indicated the failure of macroeconomic factors to adequately capture stock return variations in India, suggesting limited practical applicability of APT. Originality : The study focused on the application of APT to the Indian market using a multivariate framework, supported by PCA-based factor validation.